Integrated Crop Management for enhancing productivity and profitability - Hashim, Mohammad; Singh, C. B.; Pandey, U. C. (Indian Farming, 2015)
Integrated Crop Management (ICM) is an approach to farming which aims to balance production with economic and environmental considerations by means of a combination of measures including crop rotation, cultivations, appropriate crop varieties and careful use of inputs.